The Concept of Faith from the Perspective of Asy-Syaukani in the Book of Tafsir Fathul Qadir and Its Relevance to Faith Education in Azzhahiriyah Schools - Ismail; Neng Ulya (al-Afkar, Journal For Islamic Studies, 2026)
This research discusses the concept of faith from Abdullah Al-Syaukani's perspective in the book Tafsir Fathul Qadir and its relevance to faith education at the Azzahiriya School. This research aims to examine Asy-Syaukani's understanding of faith, which is connected to the practice of religious education in schools. Through analysis of the verses of the Qur'an relating to faith, as well as explanations of the interpretations presented by Asy-Syaukani, this research shows that faith is not only a belief in the heart, but must also be manifested in actions and worship. Apart from that, it is hoped that the application of faith values in education can shape the character of students who are disciplined and responsible. Thus, this research contributes to the development of Islamic religious education that is more effective and relevant to the needs of the times. It is also hoped that it can become a reference for educators and school administrators in integrating faith values in the educational curriculum.